Pemanfaatan Web Services Dan Microsoft Excel Untuk Pelaporan Data Neo Feeder PD DIKTI di STIKES KH Kediri - Achmad Zakki Falani; Made Kamisutara; I Putu Artaya (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2024)
Based on Circular Letters from Dirjen DIKTI No. 2332/E1.2/KP/2015 dates on 28 April 2015 explain that feeder PD DIKTI application is the only one application for  reporting data academic activities of University nationally, which is all report datas will insert from one gate via neo feeder PD DIKTI application. Related to this matter, there are minimized of socialization and ability  on University non based of Information Technology will run into various constraints for repoting data because ability of operator neo feeder PD DIKTI application who difficulty for develop Web Services (WS) has been provided by  Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi (Kemendikbud-Ristek) and also infrastructure availability is still limited. Based on this matter we do activity, there is pengabdian masyarakat (abdimas) at Sekolah Tinggi Ilmu Kesehatan (STIKES) Karya Husada in Kecamatan Pare Kabupaten Kediri. By integrating of web services neo feeder PD DIKTI and microsoft excel can give simplicity for input data academic activities in each semester by systems, there is no more input data secara manually. So that reporting data academic activities of University into  system Pangkalan Data Pendidikan Tinggi (PD DIKTI) can be done precisely, accurately and quickly.